2018
DOI: 10.4049/jimmunol.1701625
|View full text |Cite
|
Sign up to set email alerts
|

Gpr109a Limits Microbiota-Induced IL-23 Production To Constrain ILC3-Mediated Colonic Inflammation

Abstract: A set of coordinated interactions between gut microbiota and the immune cells surveilling the intestine play a key role in shaping local immune responses and intestinal health. Gpr109a is a G protein-coupled receptor expressed at a very high level on innate immune cells and previously shown to play a key role in the induction of colonic regulatory T cells. In this study, we show that mice exhibit spontaneous rectal prolapse and colonic inflammation, characterized by the presence of an elevated number of IL-17-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 63 publications
1
57
0
Order By: Relevance
“…Therefore, we isolated and cultured primary BMECs from dairy cows for subsequent experiments. GPR109A belongs to the G protein-coupled receptor family [30], which binds chemicals from the surrounding cellular environment and activates a series of signaling pathways within cells [31,32]. Studies have shown that GPR109A is highly expressed in neutrophils [33], macrophages and adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we isolated and cultured primary BMECs from dairy cows for subsequent experiments. GPR109A belongs to the G protein-coupled receptor family [30], which binds chemicals from the surrounding cellular environment and activates a series of signaling pathways within cells [31,32]. Studies have shown that GPR109A is highly expressed in neutrophils [33], macrophages and adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…SCFA can signal via multiple G-coupled protein receptors, as well as via histone deacetylase enzymes (HDAC) (43), and despite these advances the mechanisms through which SCFA regulate ILC3 are still being delineated. The SCFA receptor GPR109a was implicated in the microbiota-associated regulation of ILC3 cytokine production via the modulation of dendritic cell (DC)-derived IL-23 in the colon, although these studies largely utilized a GPR109a agonist-leaving the precise contribution of endogenous SCFA unclear (45). Interestingly, a recent study highlighted ILC3-intrinsic expression of the SCFA receptor Gpr43 (Ffar2) in the modulation of intestinal ILC3 responses (Figure 1: inputs) (46).…”
Section: Host-microbiota Sensory Circuitsmentioning
confidence: 99%
“…These benefices in intestinal inflammatory conditions such as inflammatory bowel diseases (IBD) have been demonstrated by Singh et al [ 66 ] that showed the anti-inflammatory properties of GPR109A signaling in colonic macrophages and dendritic cells, enabling them to induce differentiation of Treg cells and IL-10-producing T cells. In this way, pharmacological treatment with niacin improves colitis conditions in a GPR109A-dependent manner [ 67 ].…”
Section: Discussionmentioning
confidence: 99%